Do Refugees with Better Mental Health Better Integrate? : Evidence from the Building a New Life in Australia Longitudinal Survey - Dang, Hai-Anh H.; Trinh, Trong-Anh; Verme, Paolo (World Bank, Washington, DC, 2022)
Hardly any evidence exists on the effects of mental illness on refugee labor outcomes. This paper offers the first study on this topic in the context of Australia, one of the host countries with the largest number of refugees per capita in the world. Analyzing the Building a New Life in Australia longitudinal survey, the paper exploits the variations in traumatic experiences of refugees interacted with post-resettlement time periods to causally identify the impacts of refugee mental health. The findings show that worse mental health, as measured by a one-standard-deviation increase in the Kessler mental health score, reduces the probability of employment by 14.1 percent and labor income by 26.8 percent. There is also evidence of adverse impacts of refugees’ mental illness on their children’s mental health and educational performance. These effects appear to be more pronounced for newly arriving refugees and those without social networks, but they may be ameliorated with government support.